Asuhan Keperawatan Keluarga Dengan Tahap Perkembangan Keluarga Usia Sekolah Pada Keluarga Bapak A Khususnya Pada Ibu. L Dengan Intervensi Kompres Hangat Pada Nyeri Akut Gastritis Di Wilayah Kerja Puskesmas Periuk Jaya Kota Tangerang - Siti Solha Elmaliah; Rina Puspita Sari; M. Hasan Basri; Alfika Safitri (An-Najat, 2023)
Background: In 2023 at the Periuk Jaya Health Center, Tangerang City, gastritis ranks fourth out of the ten most common diseases at the Periuk Jaya Health Center. Management of gastritis can be done one way with non-pharmacological therapy, namely warm compresses. Applying a warm compress is an act of stimulating the skin and tissues to reduce pain. Purpose: To find out how the results of the intervention of applying warm compresses to reduce the pain scale in gastritis clients in the Periuk Jaya Health Center area. Method: Giving warm compresses to gastritis clients using a glass bottle filled with warm water with a temperature of 37-40 ℃ for 15-30 minutes. Intervention was given for 3 days of treatment once a day. Every day a pain scale was measured before and after being given a warm compress. Results: It is known that the client's gastritis pain scale before warm compresses has a moderate pain scale (4-6) and after warm compresses a pain scale of 0 (no pain) is obtained. The application of warm compresses carried out for three days had a positive effect on reducing the pain scale of gastritis clients. Conclusion: it can be concluded that this study can provide an overview of the effectiveness of applying warm compresses on reducing the pain scale of gastritis clients.